Desa Dan Otonomi Asli (Studi tentang Perangkat Desa Menuju Terciptanya Desa yang Berotonomi Asli) - Turmudi, Hadis, Prof.Dr.Harun,SH.,M.Hum, Dr.Nurhadiantomo (2017)
The existing village governance structure in village governance is a very important element, especially in realizing the original autonomous village. Where the original village autonomy is marked by the independence of villages in managing and organanizing their own households without any interference from the government or outsiders. While the purpose of this research is how the application of structure of village apparatus that exist in Indonesia through UU No.6 / 2014 and rules about village before existence of UU No.6 / 2014, and to create a concept of village infrastructure structure in the context of the creation of an original autonomous village. The results of research is the implementation of the existing village device structure Indonesia in general and Tanjungsari Village, Banyudono District, Boyolali Regency in particular has not been able to realize the original auotonomous village. This is because there is still the intervention of the district government towards the village apparatus both in terms of terms, process and full of recruitment, functions, duties and authority and the number of personnel. This study used historical approach and comparison of regulation with qualitative doctrinal method with literature review (dokumentary), observation and direct interview on several sources.